Índice multicritério de Inovação Sustentável para avaliação de pesquisas científicas em biotecnologia - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The increasing number of biotechnological research in the global and Brazilian context and the scarcity of public and private resources for investments in research and development make it critical for the actors of the national innovation system to adopt evaluation methodologies and research selection With greater innovative potential for prioritization in the allocation of resources and reduction of the risk of investment or return of the financial contribution. However, innovation, as it is directly linked to the promotion of sustainability, has the function of transforming the products and technologies used by society throughout the production chain of goods and services necessary for human consumption. In this way, sustainable innovation is the development of new products, processes, services and technologies that contribute to economic development and meeting human and institutional needs, respecting natural resources and their regenerative capacity. In this context, the problem of the present research was how to evaluate the potential for sustainable innovation of biotechnological scientific research. Therefore, the main objective was to develop an index for assessing the potential for sustainable innovation in scientific research in the field of biotechnology. To accomplish this mission, the research was divided into three distinct phases. The first one consisted in the selection of the conceptual model of the index, and the Cubo Sustainable Innovation framework was chosen because it is the most robust approach in the treatment of the effects generated by innovations orientated towards sustainability. The second step was the application of the multicriteria Analytic Network Process (ANP) to the chosen framework with the objective of making the practical use of the index possible. The third step was the practical application of the index in three different case studies. In the first case study, scientific researches were carried out to obtain and use the purple starch (Dioscorea trifida L.f) with a focus on the application of food supplements, since the evaluating company was the Complevida Produtos Naturais, which operates in this segment. In the second case study, the evaluated researches had as objective the production of bioactive extracts of agroindustrial residues of buriti (Mauritia flexuosa L.) for the manufacture of cosmetics. These surveys were evaluated by Cheiro D'Folha da Amazônia, a small company in the cosmetics sector. The third case study was carried out with the company QLuz Ecoenergia evaluating scientific research for the production of bioactive extracts of açaí agroindustrial waste (Euterpe Olereace and Euterpe Precatoria). The scientific research to obtain the purple starch obtained the score of 57.2%, the highest among those evaluated, followed by the researches of bioactive extracts of agroindustrial residues of buriti (48%) and açaí (39.6%), . The most relevant criteria were Technology, Culture, Consumption and Production and Logistics. The results showed that the scientific researches in biotechnology carried out by researchers linked to the Multi-Institutional Biotechnology Graduate Program in the Federal University of Amazonas have significant innovative potential potential, but they need adjustments to be feasible to be Produced and marketed on a production scale appropriate to the needs of the consumer markets. The main suggestions for improving the innovative potential of the research were: the construction of production units and processing of purple and / or agroindustrial residues of açaí or buriti; The promotion of marketing based on the functional properties of food and cosmetics; The participation of local communities, cooperatives or small producers as beneficiaries of the purple or agro-industrial waste of açaí or buriti; And the creation of stamps of origin linked to the Federal University of Amazonas.
Keywords: Inovação sustentável; Analytic Network Process (ANP); Pesquisa biotecnológica; CIÊNCIAS BIOLÓGICAS